(untitled) (Russian Medical and Social Journal, 2019)
The review on the use of traditional and new methods of laboratory diagnostics of fat embolism syndrome - a complication that in some cases asymptomatically accompanies severe concomitant trauma is presented. The main currently used laboratory diagnostic methods are described: traditional methods and new markers (interleukin-6, neuroglial protein S100B, surfactant protein SP-D). A review of the literature data in terms of assessing the pathogenetic and diagnostic significance of some methods of laboratory diagnosis of fat embolism syndrome, the relationship between the dynamics of the considered laboratory parameters, the clinical picture and inflammation. Own observation is presented. The results show the importance of integrating the whole range of available methods in the diagnosis of fat embolism syndrome.